Comparación de productos blanqueadores caseros naturales vs opalescence go in vitro - Girón Peñaherrera, Jhoselyn Lourdes (2025)
The use of natural at home whitening products has gained popularity because they can offer similar results to professional products. Objective: to compare the effectiveness of natural tooth whitening of sodium bicarbonate, activated charcoal and strawberry vs Opalescence Go. Methods: 28 teeth were collected and divided into 4 groups (sodium bicarbonate, activated charcoal, strawberry and Opalescen ce Go), using analysis of variance ( and Tukey test to evaluate for ten days. Results: The Tukey test dete rmined that the bleaching progress was higher for Group 4 (Opalescence go) with a colour change of 8 shades, whereas, Groups 1, 2 and 3 are simi lar to each other reaching a change between 1 to 2 shades. Conclusion: The study revealed that sodium bicarbonat e, activated charcoal and strawberry have a limited ability to lighten tooth discolouration compared to the professional whitener Opalescence Go